2023
DOI: 10.1055/s-0043-1769092
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Effusions in the Era of Immunotherapy and Antiangiogenic Therapy

Abstract: Malignant pleural effusions (MPE) have historically been associated with a poor prognosis, and patients often require a series of invasive procedures and hospitalizations that significantly reduce quality of life at the terminus of life. However, advances in the management of MPE have coincided with the era of immunotherapies, and to a lesser extent, antiangiogenic therapies for the treatment of lung cancer. Landmark studies have shown these drugs to improve overall survival and progression-free survival in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Inhibitors that block VEGF activity are thought to effectively manage MPE ( 23 ). With the promise of ICIs in lung cancer and other malignancies, there has been a renewed interest in investigating the efficacy of local and systemic ICIs for patients with MPE ( 23 , 24 ). However, ICI monotherapy for the treatment of MPE is currently not recommended, possibly due to the increased mortality associated with MPE.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors that block VEGF activity are thought to effectively manage MPE ( 23 ). With the promise of ICIs in lung cancer and other malignancies, there has been a renewed interest in investigating the efficacy of local and systemic ICIs for patients with MPE ( 23 , 24 ). However, ICI monotherapy for the treatment of MPE is currently not recommended, possibly due to the increased mortality associated with MPE.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that MPE has historically been associated with a grim prognosis. Previous studies have shown that the presence of MPE is related to reduced ICI efficacy, notably reduced OS [ 36 , 37 ]. In the era of immunotherapy and antiangiogenic therapy, future studies should focus on establishing a series of intrapleural therapies and systemic therapies to improve the OS of MPE patients.…”
Section: Discussionmentioning
confidence: 99%